2013
DOI: 10.7763/ijmmm.2013.v1.47
|View full text |Cite
|
Sign up to set email alerts
|

Novel Applications of Functionally Graded Nano, Optoelectronic and Thermoelectric Materials

Abstract: Abstract-Functionally

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…[22,151,152]. According to area of application, FGMs can be classified into biomaterial [125,[153][154][155], aerospace [156][157][158], automotive [159,160], defense [161,162], cutting tools [163], nuclear reactor [164], smart structure [165], turbine blades [166] and sports equipment [167]. Figure 10 represent an overview of the classification according to the major fields of applications.…”
Section: According To the Field Of Applicationmentioning
confidence: 99%
“…[22,151,152]. According to area of application, FGMs can be classified into biomaterial [125,[153][154][155], aerospace [156][157][158], automotive [159,160], defense [161,162], cutting tools [163], nuclear reactor [164], smart structure [165], turbine blades [166] and sports equipment [167]. Figure 10 represent an overview of the classification according to the major fields of applications.…”
Section: According To the Field Of Applicationmentioning
confidence: 99%
“…It has recently been found that the tellurium compounds Bi 2 Te 3 and Sb 2 Te 3 having ZT > 2 and PbTe based FGCs are well established thermoelectric materials suitable for use in the future [82]. A dense, graded n-type (SiGe) conversion unit produced by HIP [81].…”
Section: Fg Ceramics For Energy Applicationsmentioning
confidence: 99%
“…In the mid-1980s, a group of Japanese scientists introduced, for the first time, a new class of composites, called Functional Graded Materials (FGM) [1]. In a Functional Graded (FG) material, the composition and also the structure gradually change over the volume, which causes corresponding changes in the properties of the material [2]. As ultra-high temperature resistant materials, these types of composites are well known and widely used in many engineering applications.…”
Section: Introductionmentioning
confidence: 99%